Phosphorylation landscape of dengue virus proteins and their implications in protein-protein interactions - Prakhar Agrawal; Rahul Yadav; Arumugam Madhumalar; Ganesan Senthil Kumar (PLoS ONE, 2026)
Phosphorylation is one of the most ubiquitous, reversible post-translational modifications through which cells communicate external signals from the membrane to the nucleus. However, viruses replicate in the host cells by hijacking the phosphorylation signaling to evade immune responses, as shown previously for Ebola and HIV. Here, we characterized the potential phosphorylation sites, the kinases involved, and their location in the structure of the Dengue virus proteins. We also show that the phosphosites in the four Dengue serotypes are evolutionarily conserved across other flaviviruses. Further, we show that the phosphorylation of dengue viral proteins is critical for mediating the interaction of these viral proteins with the host proteins, antibodies, and other viral proteins. In summary, we provide an extensive resource of phosphosites across the Dengue virus/flavivirus proteins that could be leveraged to understand the role of phosphorylation signaling in viral replication and develop novel drug therapies.